Analysis on the Educational Qualification and access to Mobile Internet (Journal of Advances and Scholarly Researches in Allied Education, 2022)
One of the most rapidly rising segments of e-commerce is retail sales, which are growing at a rate of up to 50% per year, thanks in part to mobile commerce, often known as m-commerce. The main aim of the study is Analysis on the Educational Qualification and Access to Mobile Internet. Data are collected by theoretical basis and the practical means such that the characteristics of a population can be inferred with known estimates of error. With the tools available in the time window offered, this study was able to provide a complete evaluation of the effect that mobile commerce had on Kanpur's customers.